Darstellung von Zeitlichkeit in österreichischen Deutsch-Schulbüchern für die Sekundarstufe I.: Eine Analyse am Beispiel des Futur I - Ertl, Martin (Linguistik Online, 2026)
Textbooks are very important when planning and conducting lessons. This article examines the new editions of the most widely used German textbooks for the 5th and 6th grades in Austria regarding the presentation of linguistic means for the expression of temporality. The analysis is conducted as a qualitative textbook study, systematically examining and evaluating how temporal structures are presented, with a particular focus on the tense system. As an exemplary case, the study focuses on the Futur I, which serves as a key interface between temporal and modal aspects. The analysis shows that recent linguistic and didactic research results on the tense system and its teaching are only partially considered and that traditional grammar didactic concepts are still prominently represented.